The Interaction between the Antarctic Treaty System and the Other Relevant Conventions Applicable to the Antarctic Area-A Practical Approach versus Theoretical Doctrines - VIGNI, PATRIZIA (2000)
The Antarctic Treaty system seems to be a self-contained regime that is competent to regulate the management of Antarctica. Nevertheless, one must admit that third States with respect to the Treaty may prefer to apply to the area other international conventions that have been adopted in different international fora. Moreover, one must acknowledge the specialty of some international treaties that regulate some peculiar subjects such as, for example, the prevention of marine pollution. This specialty has also been recognised by the Antarctic Treaty system itself that includes some norms that are clearly inspired by these international conventions. Thus, it is not clear which norms are most suitable for application to Antarctica unless one analyses the concrete effects that the implementation of these norms provokes on the management of this peculiar area of our planet.